All types of epics that Ahmad shawqi (Journal of Hama University, 2019)
The research includes all types of epics, which Ahmad shawqi deals with. And they were sorted out into three categories:Historical stories: Talk about the history of a nation or the history of a person.Auto stories: Talk about family stories and love stories.Children stories: Deal with stories which are directed to children (or talk about them) and fables which are spoken by the tongue of animals.Then the research includes the characteristics of epics at Ahmad shawqi and ends up to:Shared properties: They are the logic chronicle and that stories with all their types include wisdom.Special characteristics to each type from the style and the content according to the differences of the purpose of the story and the group that are directed to them.